Wyznaczniki gatunku wypowiedzi na przykładzie tekstów modlitewnych - WOJTAK, MARIA (Stylistyka, 2021)
This article constitutes a linguistic attempt to characterize speech genre. The initial point of the author’s considerations is based on basic assumptions of Bachtin theory. The subject of description are numerous texts that represent the most important types of verbal prayer: established prayer, votive prayer (connected with votive cult) and poetic prayer. The characterization comprises three aspects of speech genre: structural, pragmatic and stylistic.